Cecal duplication: An unusual presentation - Monika Kaushal; Ayush Kaushal; Karthika Sasidharan; Sharmishtha Gupta (Wolters Kluwer Medknow Publications, 2021)
Background: Enteric duplication cysts are rare congenital malformations that are most commonly found in the ileum and ileocecal junction, followed by the esophagus, stomach, and duodenum. Although most present in the 1st 2 years, they are often difficult to diagnose as both presentation and radiological findings can be variable and nonspecific. Clinical Description: We present the case report of an 11-month-old child who presented with nonbilious vomiting and diarrhea. There was no fever, abdominal distension, blood in stools, or crying on defecation. A provisional diagnosis of acute gastroenteritis was kept and management started as per the standard protocol. Management: A series of investigations were carried out when the child did not improve and developed bilious vomiting. Ultrasound findings were suggestive of an ileal duplication cyst which was confirmed by magnetic resonance imaging. The child then underwent surgery where cecal duplication cyst was confirmed, which was previously missed due to a malpositioned cecum. Conclusion: Gastrointestinal duplication cysts are rare developmental anomalies that may present as an acute abdomen in a young child. The possibility of the duplication cyst should be kept as a differential diagnosis in a child presenting with unexplained vomiting, abdominal distension, or pain. Early suspicion, investigation, and intervention help in faster recovery with minimal complications.